(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the training process for acting in Specialized Educational Care (SEC) through a systematic review of the literature, in order to identify the problems that still permeate this field of action, and to reflect on the inclusive practices and policies that govern and direct SEC in the Multifunction Resource Rooms. The research results showed that the teacher education for the SEC, is not enough to fulfill all the demands attributed to the function. In addition, it was found that the training for the SEC is much more in service than in previous training, which does not prepare the professional to act in face of the reality found in schools. In view of this, it was concluded that training for SEC, initial or continuous, must accompany the advances in terms of inclusive policies, as well as in relation to the practices required of the professional who works in schools.